O sagrado e o profano: memória coletiva e literatura em “Um cordel para São Benedito”, de Dinacy Corrêa - Ferreira Filho, Luís Claudio dos Santos (2023)
A sample of the contemporary production of cordel literature, the literary work Um Cordel para São Benedito, by Dinacy Mendonça Corrêa, recounts the myth of São Benedito, who as a man found in his faith a reason to live integrally in the face of the adversities that afflicted him. His miraculous deeds were recognized by the Catholic Church after his death, which canonized him, officializing his cult throughout the European continent, being later adopted in Brazil thanks to the influence of its colonizers. However, the figure of Benedict became popular not only among the members of the Church, but also among the enslaved Afro-descendants in Brazil, who identified with his "brother of epidermis" and his afflictions. In this way, two distinct groups were instituted that have their own manifestations in honor of the saint: the group of the Church and the groups of the players of the Tambor de Crioula (Drum-of-Creole). In that literary work, these festivities have been celebrated over the decades, in what is configured as a tradition, which passes through the generations, keeping the memory of São Benedito alive within these groups, and also throughout the state of Maranhão. Therefore, it is sought to analyze the literary work Um Cordel para São Benedito from the perspective of collective memory, evaluating how the described celebrations cooperate for the memory perpetuation of the saint in the state of Maranhão, and discuss the aspects of these celebrations that cooperate for its continuity. With the theoretical support of Câmara Cascudo (1994, 2000, 2009), Galvão (2000), Grillo (2015), Haurélio (2013), Melo (1994), among others, who address the theme of cordel literature, pointing out its origin, characteristics and themes, as well as Cordeiro (2017, 2022), Halbwachs (2006) and Ricouer (2007) as a basis for the philosophical and sociological construction of the concepts of memory and collective memory, it was found that the celebrations held by the members of the Church and by the players of the Tambor de Crioula cooperate actively in the perpetuation of the collective memory of the saint, because they want, as an initial interest, to celebrate and keep alive the memory of what Benedict did as an enslaved man, as well as the miracles that he has worked today in the lives of his followers. These festive gatherings are intended to share among the members of the groups in question the blessings achieved, the prayers answered, and the requests that are being made. Finally, it is expected to contribute to studies whose research area understands literature as a historical phenomenon, establishing dialogues and establishing new meanings to identity, culture and memory.